A hollow PdCuMoNiCo high-entropy alloy as an efficient bi-functional electrocatalyst for oxygen reduction and formic acid oxidation. Issue 28 (6th July 2022) - Zuo, Xifeng; Yan, Riqing; Zhao, Linjie; Long, Yongde; Shi, Lei; Cheng, Qingqing; Liu, Dong; Hu, Chuangang
Abstract : A hollow PdCuMoNiCo high-entropy alloy on carbon hybrid was developed as a high-performance bi-functional electrocatalyst for the oxygen reduction reaction and formic acid oxidation reaction in an acidic medium. Abstract : Recently, as electrocatalysts, high-entropy alloys (HEAs) have attracted extensive research interest. In this study, a PdCuMoNiCo HEA with a nano-hollow spherical structure on RGO3 -CNTs (PdCuMoNiCo NHSs/RGO3 -CNT) was synthesized via a facile one-pot solvothermal method as a superior bi-functional electrocatalyst for formic acid oxidation (FAO) and oxygen reduction reaction (ORR). The advantage of the developed catalyst, i.e., PdCuMoNiCo NHSs on carbon hybrid, was demonstrated by its comparable ORR activity, but much better long-term durability than that of the commercial 20% Pt/C and its highest FAO performance among the reported Pd-based catalysts. It was found that its catalytic activity and stability were mainly derived from the synergistic effect of its hollow structure and HEA effect, presenting a brilliant perspective for the fabrication of HEAs as efficient bi-functional electrocatalysts with high activity and good stability.